2010
DOI: 10.1258/td.2009.090167
|View full text |Cite
|
Sign up to set email alerts
|

Rising mother-to-child HIV transmission in a resource-limited breastfeeding population

Abstract: The objective of this study was to determine mother to child HIV transmission rates at different time points in a breastfeeding cohort enrolled in a single dose nevirapine program in Harare, Zimbabwe. Between 2002-2004, 434 HIV-positive mothers and their infants were recruited and followed up from delivery to 15 months. Infant blood specimens were collected for HIV testing at these time points. The majority of the patients (78%) received single dose nevirapine. The overall HIV transmission rate was 21.8% (17.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…This coincides with the general decrease in HIV-1 prevalence in the general population and could be attributed to better access to antiretroviral prophylaxis. However, in this cohort receiving single dose nevirapine was not protective against HIV-1 vertical transmission [35]. This could possibly be due to a relatively small sample size.…”
Section: Discussionmentioning
confidence: 95%
“…This coincides with the general decrease in HIV-1 prevalence in the general population and could be attributed to better access to antiretroviral prophylaxis. However, in this cohort receiving single dose nevirapine was not protective against HIV-1 vertical transmission [35]. This could possibly be due to a relatively small sample size.…”
Section: Discussionmentioning
confidence: 95%
“…This implies that they were given better counselling and early diagnosis and treatment of mastitis which are known risk factors of HIV transmission. 10, 12 It is of note (although not statistically significant) that HIV-infected children at a subsequent pregnancy had shorter exclusive breastfeeding periods – four months versus six months for the HIV-uninfected children – while the mean duration of breastfeeding was similar (10 months).…”
Section: Discussionmentioning
confidence: 92%
“…The proportion of HIV-infected infants was 21.8% (95% confidence interval [CI] −17.8–25.8) which has been previously reported. 10 …”
Section: Methodsmentioning
confidence: 99%
“…Other challenges in dealing with HIV mother-to-child transmission not addressed by the recent better regimens are breastfeeding transmission, mortality and transmission in subsequent children. [4][5][6] …”
Section: Akmentioning
confidence: 99%
“…First, routine antenatal HIV testing ('opt-out' approach) is now the standard of care for all pregnant women presenting for antenatal care in urban and rural Zimbabwe after pilot studies evaluating opt-out HIV testing found it feasible and acceptable with significant number of pregnant women accepting HIV testing with no adverse social consequences. 3,4 Second, more efficacious PMTCT regimens are currently being implemented in urban and rural antenatal clinics to enhance PMTCT effectiveness. Third, due to severe attrition of health-care workers and limited resources, implementation of PMTCT program using peer counselors and community mobilizers has proven very effective and similar strategies are currently implemented across other PMTCT programs in Zimbabwe.…”
mentioning
confidence: 99%